Female Librarians Stereotype in the 2000s Indonesian Film - Mayesti, Nina; Salam, Aprinus; Noviani, Ratna (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2018)
This paper discusses about the research that had examined the female librarian stereotype in Indonesian films, particularly release during the 2000s. Using the paradigm of cultural and media studies, this research examined six Indonesian films portraying female librarian. The units of analysis in this study are those film scenes that were either set in a library or that portrayed female librarians. The method used to analyze the data source is the Critical Discourse Analysis. The results of this study showed that the female librarians were stereotyped in Indonesian films, such as age, dress and hair style. Librarians were depicted as an old woman with the old-fashioned dress and outdated hairstyle. The filmâs portrayal of the female librarians were representative of the stereotype in general, i.e. passive, stuffy, and orderly. But on the other hand they were depicted as a friendly, smart, helpful person, and sometimes breaking the rules. Library profession was portrayed traditionally as âlibrary-keeperâ, not as someone who plays a role in information and knowledge dissemination.